The Role of Career Planning and Career Development on Employee Performance at PT. Adira finance Ambon Branch - Asiani Sijabat (Sean Institute, 2026)
This study aims to analyze the influence of career planning and career development on employee performance at PT. Adira Finance Ambon Branch.The population in this study was all 50 employees of PT. Adira Finance Ambon Branch. The sample used was a saturated sample, where the population size is the same as the sample size.The research instrument used in this study was a questionnaire. Data analysis used Multiple Linear Regression Test. The results of this study indicate that: (1) Career Planning has a significant effect on Employee Performance, (2) Career Development has a significant effect on Employee Performance.